Interaksi Meloidogyne incognita dan Fusarium solani pada Penyakit Kuning Lada - Suryanti Suryanti; Bambang Hadisutrisno; Mulyadi Mulyadi; Jaka Widada (Jurnal Perlindungan Tanaman Indonesia, 2017)
Pepper yellowing disease is one of the most important disease of pepper causing the decrease of pepper production. This research was conducted in the screen house and laboratory to determine the major causal agent of leaf yellowing disease of pepper. Meloidogyne incognita and Fusarium solani were isolated from pepper plantation in West Kalimantan. Pepper seedlings Natar 1 cultivars were planted in sterilized soil collected from pepper plantation in Bengkayang, West Kalimantan. Five months-old seedling were inoculated with M. incognita (1000 larvae of 2nd stadium/plant) and F. solani (50 ml of spore suspension with spore density of 106 spore/ml) in several combinations of time inoculation, i.e., F. solani  and then M. incognita, M. incognita and then F. solani, M. incognita together with F. solani, M. incognita only, and F. solani only. The parameters observed were the development of leaf yellowing disease every weeks for five months. The number of gall, and population M. incognita were observed at the end of the observation. The result showed that when M. incognita was inoculated  to the roots followed by F. solani, the disease severity and the percentage of plant diseases were higher than those which were infected with F. solani or M. incognita alone. The higher population densities of M. incognita and a number of root gall, had observed on plants inoculated by M. incognita combined with F. solani than plants inoculated by M. incognita and F. solani alone. Interaction between M. incognita and F. solani as caused of leaf yellowing disease of pepper was synergistic reaction. IntisariPenyakit kuning lada merupakan salah satu penyakit penting pada lada yang mengakibatkan terjadinya penurunan produksi lada di Indonesia. Penelitian ini bertujuan untuk mengetahui peran Meloidogyne incognita dan Fusarium solani sebagai penyebab penyakit kuning lada. Penelitian yang dilakukan rumah kasa dan laboratorium. Meloidogyne incognita dan Fusarium solani diisolasi dari pertanaman lada di Kalimantan Barat. Penelitian dilakukan dengan menggunakan bibit lada kultivar Natar 1 berumur 5 bulan, dan diinokulasi dengan M. incognita sebanyak 1000 larva stadium 2 dan 50 ml suspensi mikrokonidium F. solani dengan kerapatan 106/ml. Perkembangan gejala penyakit diamati setiap minggu selama 5 bulan, dan pada akhir pengamatan dilakukan penghitungan jumlah puru dan populasi M. incognita. Hasil penelitian menunjukkan bahwa apabila M. incognita menginfeksi akar dan selanjutnya diikuti dengan infeksi oleh F. solani, tingkat keparahan penyakit dan persentase tanaman sakit lebih tinggi dibandingkan dengan infeksi oleh F. solani atau M. incognita secara terpisah. Populasi M. incognita dan jumlah puru akar pada tanaman yang diinokulasi dengan M. incognita bersama-sama dengan F. solani lebih tinggi dibandingkan pada tanaman yang diinokulasi dengan M. incognita atau F. solani secara terpisah. Interaksi antara M. incognita dan F. solani dalam menyebabkan penyakit kuning lada adalah bersifat sinergis.